2022
DOI: 10.1155/2022/7913067
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Brachyury Suppresses Breast Cancer Cell Proliferation and Migration via Targeting E2F3

Abstract: Breast cancer is one of the most frequently diagnosed cancer in women and is the major cause of most cancer-related deaths. We previously reported that Brachyury, as a sensitive and specific marker, has been verified to involve in the process of carcinogenesis and progression of breast cancer, but the mechanism by which Brachyury promotes breast cancer cells proliferation and migration still remains less clear. In this study, we identified that Brachyury was markedly increased in breast cancer compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…7 In addition, Chen et al showed that the Brachyury/E2F3 axis might be a diagnostic biomarker, and Knockdown of E2F3 diminished BC cell growth and migration. 48 Moreover, according to Jusino et al, the expression of SGO1 and E2F3 increased in invasive ductal BC compared with normal breast tissues, which correlated significantly with poor survival outcomes, epithelial-tomesenchymal transition, and metastasis. 32 Furthermore, we reported the protein-protein interaction between E2F3 and P53, and the positive correlation between them.…”
Section: Discussionmentioning
confidence: 98%
“…7 In addition, Chen et al showed that the Brachyury/E2F3 axis might be a diagnostic biomarker, and Knockdown of E2F3 diminished BC cell growth and migration. 48 Moreover, according to Jusino et al, the expression of SGO1 and E2F3 increased in invasive ductal BC compared with normal breast tissues, which correlated significantly with poor survival outcomes, epithelial-tomesenchymal transition, and metastasis. 32 Furthermore, we reported the protein-protein interaction between E2F3 and P53, and the positive correlation between them.…”
Section: Discussionmentioning
confidence: 98%
“…For the subcutaneous tumor model [ 19 ], 1 × 10 7 cells transfected with sh-NRSN2-AS1 or sh-NC were subcutaneously injected into the left and right flanks of nude mice, respectively ( n = 5). The tumor volumes were calculated every 3 days (V = 0.5 × D × d 2 (V, volume; D, longitudinal diameter; d, latitudinal diameter)).…”
Section: Methodsmentioning
confidence: 99%
“…For the subcutaneous tumor model 15 , 1×10 7 cells transfected with sh-NRSN2-AS1 or sh-NC were subcutaneously injected into the left and right anks of nude mice, respectively (n = 5). The tumor volumes were calculated every 3 days (V = 0.5 × D × d 2 (V, volume; D, longitudinal diameter; d, latitudinal diameter)).…”
Section: Xenograft In Micementioning
confidence: 99%